Effect of Phytosubstances with Antioxidant Activity on Persistence Properties of Microorganisms - O. L. Kartashova; T. M. Utkina; A. V. Zhestkov; V. A. Kurkin; P. N. Zolotarev (Антибиотики и Химиотерапия)
The in vitro effect of phytosubstances containing flavonoids and phenylpropanoids on the antilysozyme activity of varioous groups of microorganisms, such as staphylococci, bacilli, enterobacteria and nonfermenting bacteria was studied. The second fraction of the pink carbonic acid extract showed high antioxidant activity and most efficiently inhibited the ability of various microorganisms to inactivate the host lysozyme. The selected phytosubstance could be useful in clinical practice as an additional antimicrobial agent in etiotropic therapy or prophylaxis of some infections.